THE EFFECT OF PERCEIVED EASE OF USE, PERCEIVED USEFULNESS, FAMILIARITY, TRUST, AND ACTUAL SYSTEM USAGE TOWARD GOPAY AS A PAYMENT TOOL BASED ON USER IN PONTIANAK - yanto, Ariyanto B1024161012 (Jurnal Manajemen Update, 2021)
ABSTRACTThe purpose of this study was to analyze the effect of Perceived Ease of Use and Familiarity on Actual System Usage Gopay as daily payment with Perceived Usefulness and Trust as intervening variables. Currently, E-payment has become a trend due to the change in payment methods from conventional to digital. This survey research was conducted to understand the causal relationship between variables using a questionnaire as an instrument to collect data. The questionnaire was distributed to 100 samples to fulfil the requirements. The sample for this study came from the Pontianak community. In this study, the data analysis method used was the Structural Equation Model Partial Least Square (SEMPLS) method. For analysis using the PLS method, this research uses Smart PLS software (V.3.3.2). The hypothesis in this study is H1: Does perceived ease of use have a significant effect on perceived usefulness. H2: Does perceived ease of use have a significant effect on trust. H3: Does familiarity have a significant effect on trust. H4: Does perceived usefulness have a significant effect on trust. H5: Does trust have a significant effect on actual system usage. The results showed that H1, H3, H4, H5 were accepted and H2 were rejected. Keywords: Perceived Ease of Use, Familiarity, Perceived Usefulness, Trust, Actual System Usage, Gopay.REFERENCE Abend, Gabriel. "The Meaning of Theory." Sociological Theory 26 (June 2008):   173–199Abdillah, W dan Jogiyanto. 2009. Partial Least Square (PLS) Alternatif SEM   Dalam       Penelitian Bisnis . Penerbit Andi: Yogyakarta. Hal 262.Adiyanti Arsitaika. 2015. Pengaruh Pendapatan Manfaat Kemudahan Penggunaan             Daya Tarik Promosi, dan Kepercayaan Terhadap Minat Menggunakan Layanan   E-MoneyAjzen, I. 1991. The Theory of Planned Behavior. Organizational Behavior and Human     Decision Processes, 50: 179-211.Allport, G. W. (1935). Attitudes. In C. M. Murchison (Ed.), Handbook of Social             Psychology. Winchester, MA: Clark University PressAmin, Muslim. Rezaei, Sajad and Abolghasemi , Maryam . (2014). "User satisfaction       with mobile websites: the impact of perceived usefulness (PU), perceived ease   of use (PEOU) and trust". Nankai Business Review International. Vol. 5 Iss 3   pp. 258 – 274Arulchelvan and Viswanathan. 2006. Pattern of usage of various electronic media by        higher education students. (International Journal of Education and      Development using Information and Communication Technology (IJEDICT).Bianci, C., & Andrews, L. (2012). Risk, trust, and consumer online purchasing      behavior: a Chilean perspective. International Marketing Review, 29, 253-276D’Alessandro, S., Girardi, A., & Tiangsoongnern, L. (2012). Perceived risk and trust        as antecedents of online purchasing behavior in the USA gemstones industry.            Asia Pacific Journal of Marketing and Logistics, 24, 433-460.Davis. F. (1986). Technology acceptance model for empirically testing new end-user        information systems:Theory and result. Unpublished doctoral dissertation,         massachuetts institute of technology, Boston.Davis, F. D., Bagozzi, R. P., & Warshaw, P. R. (1989). User Acceptance of Computer      Technology: A Comparison of Two Theoretical Models. Management Science,      35(8), 982–1003.Davis, F.D. 1993. Perceived usefulness, perceived ease of use, and user acceptance of       information technology. MIS Quarterly, Vol.13, No.3, pp. 319-340.Fishbein, Martin and Icek Ajzen. 1975. Belief, Attitude, Intention and Behavior: An         Introduction to Theory and Research. Reading, MA: Addison-Wesley.Fung, D. (2017). How do you determine the validity and reliability of a new                      questionnaire ?Gefen, David & Straub, Detmar. (2000). The Relative Importance of Perceived Ease         of Use in IS Adoption: A Study of E-Commerce Adoption. J. AIS.                      1.0-. 10.17705/1jais.00008.Gefen, D. (2000). E-commerce: The role of familiarity and trust. Omega: International Journal of Management Science 28(6), 725-737.Ghozali, Imam. (2008). Structural Equation Modelling, Edisi II, Universitas                      Diponegoro, SemarangHadi, Musthofa & Zain, Djumilah & Sudiro, Achmad. (2016). Vendor-capacity,    Perceived-Familiarity, Perceived- Reputation, dan Personal-values sebagai             Faktor Pembeda pada Kelompok Konsumen bagi Tercapainya Online    Customers’ Trust: Studi pada Pengguna E-commerce di Indonesia. Jurnal Aplikasi Manajemen. 14. 10.18202/jam23026332.14.1.05.Hair, Jr., Joseph F., et. al. (2011). Multivariate Data Analysis. Fifth Edition. New Jersey: PrenticeHall, Inc.Indiani, Ni & Rahyuda, Ketut & Yasa, Ni & Sukaatmadja, I. (2015). Perceived Risk         and Trust as Major Determinants of Actual Purchase, Transcending The            Influence of Intention. ASEAN Marketing Journal. 7. 10.21002/amj.v7i1.4601.Kerlinger, Fred N. (1973) Foundations of Behavioral Research. 2nd edition. Holt, Rinehart and WinstonKusumah, Wijaya dan Dedi Dwitagama. 2009. Mengenal Penelitian Tindakan Kelas.        PT Indeks. Jakarta.Liébana-cabanillas, F., Sánchez-fernández, J., & Mu, F. (2014). International Journal        of Information Management The moderating effect of experience in the                  adoption of mobile payment tools in Virtual Social Networks : The m-Payment     Acceptance Model in Virtual Social Networks ( MPAM-VSN ), 34, 151–166.Leão Ramos, Fernanda & Ferreira, Jorge & de Freitas, Angilberto &                                  Werneck Rodrigues, Juliana. (2018). The Effect of Trust in the Intention to Use     m-banking. Brazilian Business Review. 15. 175-191.10.15728/      bbr.2018.15.2.5.Lee, C., & Wan, G. (2010). Including subjective norm and technology trust in the             technology acceptance model. ACM SIGMIS Database, 41(4), 40.        https://doi.org/10.1145/1899639.1899642Lim, W. M. (2013). Toward a theory of online buyer behavior using structural equation    modeling. Modern Applied Science, 7, 34-42.Lin, J dan Chang, H. (2011). The Role of Technology Readiness In Self-Service                Technology Acceptance. Managing Service Quality: An International Journal,   21(4), 424 – 444.Maroofi, Fakhraddin & Kahrarian, Fatemeh & Dehghani, Marzieh. (2013). An                  Investigation of Initial Trust in Mobile Banking. International Journal of                  Academic Research in Business and Social Sciences. 3. 10.6007/IJARBSS/v3     -i9/228.Mcknight, D. & Choudhury, Vivek & Kacmar, Charles ("Chuck"). (2002). The Impact     of Initial Consumer Trust on Intentions to Transact with a Web Site: A Trust      Building Model. The Journal of Strategic Information Systems. 11. 297-323.    10.1016/S0963-8687(02)00020-3.Park, S.Y. (2009). An Analysis of the Technology Acceptance Model In Understanding   University Students Behavioral Intention to Use e-Learning. Educational            Technology & Society, 12(3), 150–162.Premkumar, G., Ramamurthy, K., & Liu, H. N. (2008). Internet messaging: An     examination of the impact of attitudinal, normative, and control belief systems. Information and Management, 45(7), 451–457Research Variables: Dependent, Independent, Control, Extraneous & Moderator.   (2013, September 14). Retrieved from            https://study.com/academy/lesson/research-variables-dependent-independent-            control-extraneous-moderator.html.Ridwan. (2004). Belajar mudah penelitian untuk Guru-Karyawan dan Peneliti Pemula.      Bandung : AlfabetaSaintz ,Jocellynne. (2019). Analisa Pengaruh Initial Trust Terhadap Actual Usage             Melalui Behavioral Intention Dalam Aplikasi Digital Payment Ovo. Fakultas     Ekonomi Universitas Kristen Petra.Sari, Septi & Widyanti, Ratri & Listyorini, Inon. (2020). Trust and Perceived Risk                        toward Actual Online Purchasing: Online Purchasing Intention as Mediating          Variable. Integrated Journal of Business and Economics.                                           4.61.10.33019/ijbe.v4i1.248.Sekaran, U., and Bougie, R. 2009. Research Methods for Business, A skill building           approach. Fifth Edition. WileyShareef, M.A., Archer, N., Fong, W., Rahman, M.O., & Mann, I.J. (2013). Online             buying behavior and perceived trustworthiness. British Journal of Applied                       Science & Technology, 3, 662-683.Sugiyono. (2005). Memahami Penelitian Kualitatif. Bandung: CV. Alfabeta.Sugiyono. (2015). Metode Penelitian Kombinasi (Mix Methods). Bandung:           CV.Alfabeta.Sugiyono. (2016). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: CV.       Alfabet. Sugiyono. (2017). Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: CV.       Alfabeta.Swanson, Richard A. Theory Building in Applied Disciplines. San Francisco, CA:            Berrett-Koehler Publishers 2013.Pan, Y. N., & Zinkhan, G. M. (2006). Exploring the impact of online privacy disclosure   on consumer trust. Journal of Retailing, 82, 331-338.Vinzi, V.E, et al. (2010). Handbook of Partial Least Square: Concepts Methods and          Application Germany: Springer.Venkatesh, V. (2000). Determinants of Perceived Ease of Use: Integrating Control,           Intrinsic Motivation, and Emotion into the Technology Acceptance Model.          Information System Research, 11(4), 342-365Wibowo, Arief. 2006. Kajian tentang Perilaku Pengguna Sistem Informasi dangan            Pendekatan Technology Acceptance Model(TAM). Fakultas Teknologi Informasi, Universitas Budi Luhur